Anorexia nervosa in adolescent girls: variants of the disease, recurrence factors and suicidal risk at early stages of treatment - A. A. Pichikov; Y. V. Popov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The outcomes of adolescent anorexia nervosa depend not only on the clinical dynamics of the disorder itself but also on the kinds of treatment, which can sometimes adversely affect the course of the disease. This is due to several unaccounted factors, which can be prognostically adverse and can facilitate the relapse of anorexia nervosa at a young age. Both a large number of relapses and the general duration of hospital treatment indicate a possibility of adverse outcome, which can be seen in about 30% of the cases in clinical practice. The article contains clinical observations based information on common variants of the course of anorexia nervosa in females at the beginning of treatment, the frequency of relapses and their determining factors.